REGISTER OF FASHION CONTENT CREATION ON INSTAGRAM - Ali, Allisya Zahra; Suyatman, Ujang; Ruminda, Ruminda (PARADIGM: Journal of Language and Literary Studies, 2024)
Social media is one of the reasons a has language revolutionized, leading to the formation of new words as well as a shift in the meaning of a word. This research reveals new insights that resulted from the influence of a specific community and the language trends that this community created. It is the register used by the community of fashion content creators on Instagram. In this paper, the researchers analyzed the process of word formation and semantic change. The fashion content creator community is chosen because it is considered interesting and there is a lot of interaction between fashion content creators and their audience. Interactions and trends led to the occurrence of the possibility of new word formations and semantic changes in the registers. This qualitative research employed documentation as its data collection technique. The data of this research are the registers among the fashion content creators on Instagram social media application. The results of this research found thirty registers related to fashion content, including perf (which means “perfect”), inspo (which means “inspiration), OOTD (which is an abbreviation of “outfit of the day”), preloved (which means second hand clothes or items), etc. Among these thirty registers, it was found that sixteen of them were through a word formation process. Meanwhile, the other fourteen registers went through the semantic change process. The usage of registers in the fashion content creator community on Instagram is influenced by gender, the topic of the conversation, the purpose of communication, the social context, and the medium of communication. This research provides a detailed view of how specific online communities develop unique registers by analyzing the utterances and practices of fashion content creators on Instagram.